1993
DOI: 10.1007/bf01425693
|View full text |Cite
|
Sign up to set email alerts
|

Thermionic emission from fullerenes

Abstract: Abstract. We investigate the time dependence of carbon cluster ions, formed via thermionic emission from photoexcited fullerenes (C60 and C70 ). By pulsing the extraction field, we are able to observe delayed ions formed as late as 100 #s after excitation at 532 nm, 355 nm, or 266 nm. All even-sized clusters in the range 36 _< n -< 70 undergo thermionic emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Although the different peak heights in Fig. 1 designated 56 21 give already some indication on the relative probability of the sequential reaction (2a) as compared to the direct ejection of an intact C 4 unit (i.e., the sequential decay as witnessed by peak 56 21 in the bottom panel is about a factor of 4 stronger than the decay C 21 60 to C 21 56 in the 2ff region), due to the unknown discrimination in the 1ff and 2ff regions and the occurrence of competing decay processes such as the emission of photons [30,31] (radiative cooling) and the emission of electrons [32] (delayed ionization), it is not possible to analyze quantitatively the data shown in Fig. 1.…”
mentioning
confidence: 99%
“…Although the different peak heights in Fig. 1 designated 56 21 give already some indication on the relative probability of the sequential reaction (2a) as compared to the direct ejection of an intact C 4 unit (i.e., the sequential decay as witnessed by peak 56 21 in the bottom panel is about a factor of 4 stronger than the decay C 21 60 to C 21 56 in the 2ff region), due to the unknown discrimination in the 1ff and 2ff regions and the occurrence of competing decay processes such as the emission of photons [30,31] (radiative cooling) and the emission of electrons [32] (delayed ionization), it is not possible to analyze quantitatively the data shown in Fig. 1.…”
mentioning
confidence: 99%
“…These observations imply that not only C 60 , but also the smaller fragments exhibit delayed ionization. In our previous work, using pulsed ion extraction, we have unambiguously shown that fragment ions down to C 36 do, indeed, undergo delayed ionization [8].…”
Section: Resultsmentioning
confidence: 96%
“…with quantities which would tend to change the distribution of internal excitation energy [8]. Elsewhere it will be shown that delayed ionization of C 60 is best described by a continuum of rate constants, leading to a simple power law dependence [18].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This also implies that that they may escape the post-photoionisation zone of the TOFMS. In addition, formation of ionised metastable fullerene fragments may actually be preferred as a result of the competition between thermionic electron emission (Campbell et al 1991(Campbell et al , 1992Walder et al 1993) and dissociation through C 2 emission during relaxation of the emitted hot fullerenes from the ion track. In the ISM, the formation of the fullerenes may be triggered by the cosmic rays and subsequently emitted from the highly excited core region of the ion tracks.…”
Section: Pahs and Fullerenes Released By Cosmic Radiationmentioning
confidence: 99%